(untitled) (Marketing Journal, 2026)
Abstract The article analyzed investment directions in the digital economy and their impact on economic growth. Global investment volumes in fintech, e-commerce, artificial intelligence, cloud infrastructure, and cybersecurity were examined. Sectoral development trends and levels of investment activity were assessed. The expansion of the digital economy in Southeast Asia was reviewed. Key risk factors within the investment environment were identified and their priority levels were evaluated. The findings demonstrated the high return potential of digital markets. It was substantiated that sustainable development was ensured through risk management, diversification, and strategic investment planning. Keywords: digital economy, investment, fintech, AI, cybersecurity, e-commerce, cloud computing, digital infrastructure.